2017
DOI: 10.1002/lno.10773
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling indicators of water quality due to the invasive zooplankter, Bythotrephes longimanus

Abstract: Cultural eutrophication of lakes due to excess loading of nutrients is a global problem affecting the provisioning of freshwater ecosystem services. Lake water quality is often described by trophic state indicators such as water clarity or concentrations of nutrients, chlorophyll, and cyanobacteria toxins. While these indicators are widely assumed to covary, capturing the same basic aspects of water quality, they can be uncoupled by changes in lake food webs. Outbreak of the invasive predatory zooplankton, Byt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
(92 reference statements)
0
17
0
Order By: Relevance
“…m −3 ). Walsh et al (2018) found that D. pulicaria biomass declined in Lakes Mendota and Monona after Bythotrephes invasion, but to a much greater extent in Lake Mendota. Because Lake Monona has been managed as a “panfish” or zooplanktivore lake while managing Lake Mendota as a “gamefish” or piscivore lake (i.e., strict regulations on harvest of piscivorous fishes) (Lathrop et al 2002; Walsh et al 2017), Bythotrephes may be controlled by planktivorous fish, such as bluegill, in Lake Monona.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…m −3 ). Walsh et al (2018) found that D. pulicaria biomass declined in Lakes Mendota and Monona after Bythotrephes invasion, but to a much greater extent in Lake Mendota. Because Lake Monona has been managed as a “panfish” or zooplanktivore lake while managing Lake Mendota as a “gamefish” or piscivore lake (i.e., strict regulations on harvest of piscivorous fishes) (Lathrop et al 2002; Walsh et al 2017), Bythotrephes may be controlled by planktivorous fish, such as bluegill, in Lake Monona.…”
Section: Discussionmentioning
confidence: 99%
“…In the summer of 2009, the invasive predatory zooplankton, spiny water flea (B. cederströmii) was detected in Lake Mendota and Lake Monona. In subsequent years, D. pulicaria biomass was notably lower, resulting in reduced water clarity especially in Lake Mendota (Walsh et al 2017(Walsh et al , 2018.…”
Section: Study Lakesmentioning
confidence: 99%
See 3 more Smart Citations